Metabolic Vulnerabilities and Epigenetic Dysregulation in Myeloproliferative Neoplasms - Sharma, Vasundhara; Wright, Kenneth L.; Epling-Burnette, Pearlie K.; Reuther, Gary W. (Frontiers in Immunology, 2020)
The Janus kinase 2 (JAK2)-driven myeloproliferative neoplasms (MPNs) are associated with clonal myelopoiesis, elevated risk of death due to thrombotic complications, and transformation to acute myeloid leukemia (AML). JAK2 inhibitors improve the quality of life for MPN patients, but these approved therapeutics do not readily reduce the natural course of disease or antagonize the neoplastic clone. An understanding of the molecular and cellular changes requisite for MPN development and progression are needed to develop improved therapies. Recently, murine MPN models were demonstrated to exhibit metabolic vulnerabilities due to a high dependence on glucose. Neoplastic hematopoietic progenitor cells in these mice express elevated levels of glycolytic enzymes and exhibit enhanced levels of glycolysis and oxidative phosphorylation, and the disease phenotype of these MPN model mice is antagonized by glycolytic inhibition. While all MPN-driving mutations lead to aberrant JAK2 activation, these mutations often co-exist with mutations in genes that encode epigenetic regulators, including loss of function mutations known to enhance MPN progression. In this perspective we discuss how altered activity of epigenetic regulators (e.g. methylation and acetylation) in MPN-driving stem and progenitor cells may alter cellular metabolism and contribute to the MPN phenotype and progression of disease. Specific metabolic changes associated with epigenetic deregulation may identify patient populations that exhibit specific metabolic vulnerabilities that are absent in normal hematopoietic cells, and thus provide a potential basis for the development of more effective personalized therapeutic approaches.